Brightening the Prospects of Virtue Ethics in Business: Reflections from Theology - Wong, Kenman L. (Christian scholar's review, 2024)
Virtue ethics has made impressive inroads into the business academy. However, the prospects of the development of virtues in the actual practice of business remain in doubt. Among the most influential skeptics is Alasdair MacIntyre, who argues that business institutions must focus on "external goods" (material rewards and prestige) which threaten the development of "internal goods" (excellence, the well-being of others) necessary to form virtues. In this paper, I turn to theology to bolster the prospects of virtue ethics, focusing especially on how organizational policies and practices shape the moral and spiritual dispositions of employees. A business that one long-term employee describes as "what would happen if a monastery became a tech firm" will be discussed as an exemplar of how a business can embody the kind of "community of practice" needed to form the character of employees positively.